2011
DOI: 10.15835/nbha3926276
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Comparison of Pinus brutia Ten. Populations from Different Elevations by RAPD Markers

Abstract: Turkish Red Pine (Pinus brutia Ten.) is an important forest tree species in Turkey for various economic and ecological reasons. In this study, nine RAPD (Randomly Amplified Polymorphic DNA) primers were used to determine genetic variation within and among populations of P. brutia located at the Duzlercami common-garden test site. This site was established in 1979 and includes six natural populations of P. brutia from two altitudinal transects extending from the coast to higher elevations in the Antalya region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(54 reference statements)
0
13
0
3
Order By: Relevance
“…It plays an important role in biological diversity, and lays a foundation for the ecological system's diversity and species diversity. The high or low genetic diversity of a species reflects its ability to adapt to the environment changes, and the level of the diversity directly affects the survival and potential evolution of species Kurt et al, 2011). Genetic diversity can significantly change with the variation of altitudes that regulate ecological conditions in a particular habitat of the plant (Erich and Johann, 2002;Semang et al, 2003;Feng et al, 2004;Kurt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays an important role in biological diversity, and lays a foundation for the ecological system's diversity and species diversity. The high or low genetic diversity of a species reflects its ability to adapt to the environment changes, and the level of the diversity directly affects the survival and potential evolution of species Kurt et al, 2011). Genetic diversity can significantly change with the variation of altitudes that regulate ecological conditions in a particular habitat of the plant (Erich and Johann, 2002;Semang et al, 2003;Feng et al, 2004;Kurt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The high or low genetic diversity of a species reflects its ability to adapt to the environment changes, and the level of the diversity directly affects the survival and potential evolution of species Kurt et al, 2011). Genetic diversity can significantly change with the variation of altitudes that regulate ecological conditions in a particular habitat of the plant (Erich and Johann, 2002;Semang et al, 2003;Feng et al, 2004;Kurt et al, 2011). Consequently, a change pattern of genetic diversity in plant populations along an altitude for theoretical interests, utilization and conservation altitude can cause a drastic change in environmental gradient becomes an increasingly attractive subject both Williams, 1979;Baur and Raboud, 1988; Agar et practices because sometimes a relatively small change in al.,2012).Now, some studies have shown that the level of conditions, such as temperature and moisture (Heath and genetic diversity of plant populations decreases or increases along altitudinal gradients (Premoli, 2003).However, there are also researches indicating opposite results, the genetic differentiation within populations fluctuate to a large extent (Li et al, 1998) or do not correlate (Saenz-Romero and Tapia-Olivares, 2003) with an increase in altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have been widely used in genetic analyses, breeding studies and investigations of genetic diversity and the relationship between cultivated species and their wild parents (Kurt et al, 2011;Mokrani et al, 2012;Sofalian et al, 2009). This is because they have several advantages as compared to morphological markers, including detecting high polymorphism and independence from effects related to environmental conditions and the physiological stage of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, en el presente trabajo se utilizan los marcadores de RAPD, para evaluar la variación de sus poblaciones norteñas, inlcuyendo las más septentrionales y exclusivamente las que ocurren en la Sierra Madre Oriental, además se considera, por primera vez, una población recientemente registrada en el estado de Nuevo León. Analizar solo la parte norte de la distribución de las especies dará la oportunidad de conocer, si existe una estructura poblacional, así como evaluar las poblaciones más septentrionales y las más aisladas.Los marcadores nucleares RAPD se han usado para analizar la variación genética de especies y poblaciones del género Pinus (Newton et al, 2002;Kurt et al, 2011; Cipriano et al, 2013; Kovacevic et al, 2013; Zhang et al, 2013); así como para reconstruir la relación filogenética de algunos taxa (Favela, 2004; Castro-Félix, 2008). La técnica de RAPD no requiere previo conocimiento del genoma por utilizar, tienen, además, la ventaja de ser marcadores multilocus arbitrarios que generan un gran número de marcadores polimórficos por la amplificación o no amplificación de secuencia de ADN dispersos por todo el genoma (Williams et al, 1990; Vos et al, 1995), de los cuales se obtiene información más precisa de la que se infiere basada en un solo gen (Koopman, 2005).…”
unclassified
“…Los marcadores nucleares RAPD se han usado para analizar la variación genética de especies y poblaciones del género Pinus (Newton et al, 2002;Kurt et al, 2011;Cipriano et al, 2013;Kovacevic et al, 2013;Zhang et al, 2013); así como para reconstruir la relación filogenética de algunos taxa (Favela, 2004;Castro-Félix, 2008). La técnica de RAPD no requiere previo conocimiento del genoma por utilizar, tienen, además, la ventaja de ser marcadores multilocus arbitrarios que generan un gran número de marcadores polimórficos por la amplificación o no amplificación de secuencia de ADN dispersos por todo el genoma (Williams et al, 1990;Vos et al, 1995), de los cuales se obtiene información más precisa de la que se infiere basada en un solo gen (Koopman, 2005).…”
unclassified